Designing Lessons to Help Turkish Middle School Students Learn about Orthogonal and Isometric Drawings of Three-dimensional Shapes - Saralar, Ipek (2020)
This thesis describes a design-based research project to develop, implement and evaluate lessons intended to help middle school students learn about three-dimensional shapes and in particular orthogonal and isometric drawings of polycubes.